(untitled) (Prostor, 2023)
This study examines the impact of internships and the influence of construction site manager (CSM) as a role model on students’ educational and career paths, employing Kolb’s experiential learning theory as a theoretical framework. To address the research objectives, a questionnaire was conducted on 93 architecture students, focusing on four key research questions: (1) Does the internship experience affect students’ perception of CSMs? (2) Does it influence their career goals related to CSM positions? (3) Does the internship experience alter the career aspirations of intern students regarding the career as a construction site manager? and (4) Do students perceive CSMs as role models after completing their internships? The findings show how internships significantly affect students, improving their comprehension of the CSM role, influencing their aspirations for their careers, and offering life-changing experiences. It is anticipated that these findings will significantly advance the field of architecture education and have applications in curriculum development, internship program design and execution, and career counseling services, especially in underdeveloped or developing countries.